The level of motor ability of soccer athletes in the FC UNY Academy in 2020 - Yudanto Yudanto; Tifa Alfian (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2020)
This research aims to find out the level of motor ability of the Football Athlete at the FC UNY Academy in 2020. The purpose of this study was to determine the level of motor ability of the Football Athlete at the FC UNY Academy in 2020. This research was a quantitative research with survey method. The research population was 24 Soccer players from Yogyakarta State University FC Academy in 2020. The test instruments used in this study are using the Barrow motor ability test which includes: Standing broad jump , Soft ball throw , Zigzag run , Wall pass , Medicine ball put , Running 60 yard dash. Measuring instruments used to measure are stopwatch and meter. Data analysis techniques using descriptive analysis with percentage. The results of the research on the motor ability level of Football Athletes at the FC UNY Academy in 2020 as the following: 2 athletes (8.33%) are in very high category, 2 athletes (8.33%) are in high category, 10 athletes (41.67 %) are in moderate category, 8 athletes (33.33%) are in poor category, 2 athletes (8.33%) are in very poor category. Tingkat kemampuan motorik atlet sepakbola di Akademi FC UNY tahun 2020 AbstrakPenelitian ini bertujuan untuk mengetahui seberapa tingkat kemampuan motorik Atlet Sepakbola Di Akademi FC UNY Tahun 2020. Tujuan dari penelitian ini yaitu untuk mengetahui tingkat kemampuan motorik Atlet Sepakbola Di Akademi FC UNY Tahun 2020. Penelitian ini merupakan penelitian kuantitatif. Metode penelitian yang digunakan adalah metode survei dengan teknik tes pengukuran untuk mendapatkan data. Populasi yang digunakan dalam penelitian ini adalah Atlet Sepakbola Di Akademi FC UNY Tahun 2020 yang berjumlah 24 orang. Instrumen tes yang digunakan dalam penelitian ini yaitu menggunakan tes Barrow motor ability test yang meliputi: Standing broad jump, Soft ball throw, Zig-zag run, Wall pass, Medicine ball put, Lari 60 yard dash. Alat ukur yang digunakan untuk mengukur adalah stopwatch dan meteran. Teknik analisis data menggunakan analisis deskriptif dengan persentase. Hasil dari penelitian tingkat kemampuan motorik Atlet Sepakbola Di Akademi FC UNY Tahun 2020 sebagai berikut bahwa 2 atlet (8,33%) berada pada kategori sangat tinggi, 2 atlet (8,33%) berada pada kategori tinggi, 10 atlet (41,67%) berada pada kategori sedang, 8 atlet (33,33%) berada pada kategori kurang, 2 atlet (8,33%) berada pada kategori sangat kurang.